Identification of Endophyte Plant Growth Promoting Rhizobacteria from Rice Root Systems Based on Morphological Characters - Yugi R. Ahadiyat (Gontor AGROTECH Science Journal, 2020)
Endophytic bacteria have some benefits including N-fixation from the air, produce phytohormones such as auxin and cytokines, and stimulate growth. The objective of this study was to obtain endophytic bacterial isolates based on their morphological characteristics from the roots of rice plants. Sampling was taken at three different places in the rice planting area in the Bobosan District, Banyumas Regency and Tidar District, Magelang Regency. Sampling was observed on endophytic bacteria based on micro and macro morphological characters. The results showed that there was a diversity of microscopic morphological characters in size and macroscopic morphological characters in colony surface and color. Endophytic bacteria identified as having potential as Plant Growth Promoting Rhizobacteria..